Different approach techniques in volleyball spike - Kuhlmann, C. H.; Roemer, K.; Milani, T. L. (North American Congress on Biomechanics, University of Ottawa, 2008)
In volleyball spikes the impact height of hand nd ball is a relevant parameter for success (Tillman et al., 2004). A higher ball impact location allows more possibilities for technical and tactical variation. Therefore, the optimisation of jump height (JH) is in the focus of research. In the literature coherencies between different parameters of lower limb to the JH were analysed (e.g. Coutts, 1982). However, most of the published studies have been performed under laboratory conditions. The purpose of this study was to analyse if a coherency to JH could be found in selected arameters of the lower limb (e.g. foot angle at take off) in top-level athletes under contest conditions.